Korespondensi Fonemis Bahasa Melayu Makassar, Bahasa Mandar, dan Bahasa Bugis - Rizki Amalia Sholihah (Kantor Bahasa Provinsi Maluku Utara, 2015)
This research focuses on Makassar-Malay language, Buginese language, and Mandar language. Those three languages share similarity and difference from phonological overview indicating the languages originated from the same proto language and have a close kinship. Generally, this research gives some information about Makassar-Malay, Buginese, and Mandar languages for the research of comparative historical linguistics in Indonesia, and specifically the research analyze the phonemic correspondence among the three languages.The data are analyzed by using qualitative approach with the method of comparison. This method aims to determine the sound nature (sound correspondence) of 250 basic vocabularies of Makassar-Malay language, Buginese language, and Mandar language which have the same meaning (one gloss). If there is more than oneword in the glosses (synonym) of one language so the word which is taken as the data in this study is the word that has the same form or similar with its proto language.The technique used is phonemic correspondence device determination and correspondence formula determination. Of 250 glosses selected, 105 glosses have phonemic correspondence. The correspondence which have been found through this research are /ә a/, /a ә/, /u ɔ/, and /b w/. Besides, It can be known that Makassar Malay language is closer related to Mandar language than Bugis language.